Presenting a Model for Examining the Impact of IT on Organizational Productivity based on Process- Oriented Approach - Seyed Mohammad Moghimi; Mashaalah Hoseinzadeh (Journal of Information Technology Management)
Promoting productivity is one of the goals of usinginformation technology in organizations. The purpose of this research isexamining the impact of IT on organizational productivity andrecognizing its mechanisms based on process-oriented approach. For thisend, by reviewing the literature of the subject a number of impacts of ITon organizational processes were identified. Then, through interviewswith IT experts, seven main factors were selected and presented in aconceptual model. This model was tested through a questionnaire in 148industrial companies. Data analysis shows that impact of IT onproductivity can be included in the eight major categories: Increasing ofthe Automation, Tracking, Communication, Improvement, Flexibility,Analytic, Coordination and Monitoring in organizational processes.Finally, to improve the impact of information technology onorganizational productivity, some suggestions are presented.